UJI POTENSI FUNGI PELAPUK PUTIH ASAL BATANG KAYU EUKALIPTUS (Eucalyptus grandis ) SEBAGAI PENDEGRADASI LIGNIN - Gepsy Onardo Silaban; Edy Batara Mulya Siregar; Lutfhi Hakim (Peronema Forestry Science Journal, 2016)
Lignin is a polymer which has heterogen and complex structure and composed of alcohol coniferil, alcohol sinaphil, and alcohol kumaril so that hard to change. This research aimed to get white rot fungi isolat at eucalyptus wood and measure the ability of Lignin Peroksidase Enzim (LiP) of white rot fungi from eucalyptus wood as degrading lignin. Sample was get from Kesatuan Pengelolaan Hutan Lindung Tobasa area, North Sumatera. Type of white rot fungi originated from Eucalyptus grandis was Phanerochaete sp.1, Phanerochaete sp.2, and Exidia sp. Based on mend of LiP activity result, Exidia sp was the most potential for biopulping because it has highest activity point about 0,037 (U/MI). Key word : lignin peroksidase, eucalyptus wood, Bavendamm test, LiP test